Identification of IT-service metrics for a business process when planning a transition to outsourcing - Šimonová, Stanislava (IEEE (Institute of Electrical and Electronics Engineers), 2016)
Business processes, especially key value-add processes, need to be supported by targeted and relevant information services to ensure high performance. Company management perceives information services as a necessary part of the business process and expects their continuous performance. Therefore, the cost of IT technologies represents a significant item in company budget. This places executives into a contradictory position. On one hand, they should increase efficiency and decrease cost; on the other hand they need to devote financial/human/technological resources to develop information services as the company information environment needs to be flexibly adapted to the needs of the changing markets. Developing of internal information environment by own resources is demanding and it takes sources of the company which could be devoted to its primary activities. One of the solutions for this situation is outsourcing, however transition to outsourcing is related to many risks. They include the transition to a new mode of service providing, the necessity to include the relation "external service provider - internal service customer", selection of correct type of outsourcing and suitable external provider. The greatest risk is connected with defining the service parameters in contractual relationship for ensuring service quality; this risk is related to identification of these service quality parameters. This text focuses on defining the assumptions for monitoring of information services quality within information processes which are selected for outsourcing. A method is modelled which identifies the metrics that will become the base for definition of information services quality parameters.
Identifikace metrik IT služby pro business proces při plánování přechodu na outsourcing
Keywords: IT quality management; IT service metrics; transition IT services to outsourcing; IT mnagement kvality; metriky IT služeb; přechod IT služeb na outsourcing